Characterization of AGAMOUS Ortholog and Promoter from the Ilex verticillata (Aquifoliaceae) - Jiayi Li; Yalan Su; Xiangjian Chen; Zhixiong Liu (Horticulturae)
Arabidopsis AGAMOUS (AG) plays a crucial role in specifying stamen and carpel identities, floral meristem identity determination, and repression of the A-function. Ilex verticillata (Aquifoliaceae) is a dioecious shrub, whereby an individual plant has either male or female flowers with vestigial organs of the opposite sex. The molecular mechanism of male and female organ development in I. verticillata remains unknown. In order to identify the possible roles of AG-like genes in regulating floral development in I. verticillata, AG ortholog (IlveAG) and its promoter (pIlveAG) from the male and female flowers of I. verticillata were separately isolated. IlveAG is highly expressed in stamens, pistils, and sepals of male and female flowers. Moreover, obvious GUS staining was observed in the inflorescence and sepals, stamens, and pistils of mature flowers in pIlveAG::GUS Arabidopsis. The 35S::IlveAG Arabidopsis showed obviously early flowering. Moreover, IlveAG could substitute for endogenous AG to rescue the stamen and pistil in the Arabidopsis ag-1 mutant. In addition, expression of IlveAG can inhibit the development of sepals and petals (two outer whorls of floral organs) in wild-type and ag-1 Arabidopsis. Our findings suggest that IlveAG has a conservative C-function and plays key roles in determination of reproductive floral organs (stamen and carpel) identity and meristem determinacy. Our results provide more details to understand the role of AG orthologs in the development of male and female flowers in woody plants.